'I need somebody to hear me': YouTube and identity expression of biracial individuals. (3rd April 2017) - Patterson, Ashley
Abstract: The first time multiracial individuals were afforded the opportunity to identify with more than one race on the US Census was in the year 2000. Between 2000 and 2010, the black-white multiracial subpopulation was the largest and fastest growing within the two or more races category. The identities of many within this particularly youthful group are being formed within the digital world of social media, what has become a platform for individuals to share their personal truths with real and imagined audiences. Thus, a mapping of the current identity expression landscape must consider uses of digital media. This article takes up this task through a critical discourse analysis through a critical discourse analysis of a selection of YouTube video commentaries posted by black-white biracial individuals. As individuals describe experiences had in educational spaces, they also communicate beliefs about their identities – the ways they see themselves and the ways they want to be seen.